A study of the security concerns and policies of Asian developing countries with regard to sustainable development and impact of nuclear energy - Devi Rani Bindu (African Journal of Environmental Economics and Management, 2017)
The problem of global climate change will be solved by meeting stringent, long-term policy targets that are much more ambitious than the short-term, greenhouse gas emission reductions that some countries currently attempt to reach. The large-scale implementation of carbon-free technologies constitutes one of the measures essential to realize the mitigation of global warming. Nuclear power generation involves no carbon dioxide emissions, but the current use of nuclear energy cannot be considered sustainable. However, in attempting to achieve sustainable development - and to establish transition paths towards sustainable energy systems in particular - nuclear energy might, for the moment, need to remain a component of the global energy mix. Asian developing countries, aspiring to embark upon paths of rapid economic growth and to increase levels of welfare, should carefully consider the relatively high costs involved in the development of nuclear power when designing long-term, sustainable, and affordable energy infrastructure. This paper argues that if countries such as China and India continue to expand the use of nuclear energy, they would do better not to choose a nuclear fuel cycle based on reprocessing, but to adopt a once-through fuel cycle instead.